DEVELOPMENT OF AN ENVIRONMENTALLY-FRIENDLY LOGISTICS MODEL BY INTEGRATING DECISIONS OF LOCATION, MULTI-CAPACITY VEHICLE, AND ROUTING PROBLEM - Artya Lathifah; Sinta Rahmawidya Sulistyo; Izzawi Winda Murti; A.A.N Perwira Redi (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2018)
Transportation and distribution are two things that are closely related to logistics problems However, on the other hand this activity can sometimes damage the environment. Emissions from fuels used in transportation and distribution activities accounted for 29.4% of the total costs incurred by the organization in their activities. From this issue many organizations finally make environmentally friendly logistics as priority in their activities, where the goal of minimizing distribution costs and maintaining sustainability of environments. Some factors that can be improved are: determination of the location depot, combination of vehicle and the route. Therefore, this study aims to develop mathematical model that optimize these three factors integration to minimize the emission cost. The results of this research are the mathematical model, optimization of the development of the Simulated Annealing (SA) method that is applied to the problem is able to get a reduction in total emissions costs up to 18.8%.